A comparison Between Elzaki Transform and Laplace Transform to Solve ODE's and Systems of ODE's (Journal of Humanitarian and Applied Sciences, 2018)
In this paper Elzaki transform was compared with Laplace transform in solving some ODE's and systems of ODE's
Keywords: Laplace transform; Elzaki transform; Differential Equation